The Annexation of Crimea by the Russian Federation. Before, behind and beyond the Conflict - Marsili, M. (26th IPSA World Congress of Political Science (26th IPSA WC2021), 2021)
In 2014 a violent conflict inflamed Crimea, an autonomous republic within Ukraine, resulting in the destabilization of regional security. The clash between the government of Kiev and the insurgents led to the annexation of Crimea and Sevastopol by the Russian Federation. This paper traces origins and causes of the conflict and tackles the issue of the right to self-determination and independence, then the question of the recognition of a new state entity, and finally the dissolution by incorporation into another state. Through a comparative analysis of some precedents, this article aims to investigate whether the annexation may be regarded as legal or not under international positive and customary law, what are the remedies available, and the likely outcome of the dispute, ending with some recommendations aimed at a settlement of the crisis.